Strategi Pemasaran Produk Tapai Gambut Sebagai Bahan Ajar Mata Pelajaran Dasar-Dasar Pemasaran Pada Materi STP Marketing Di SMKN 3 Banjarmasin - Khadijah Khadijah; Muhammad Rahmattullah; Monry Fraick Nicky Gillian Ratumbuysang; Dwi Atmono (Pendidikan IPS FKIP ULM, 2022)
Marketing strategies are an important factor for successful bussines today, where marketing strategies are the way to achieve business goals. Marketing strategy is the primary approach used by business units in achieving goals that include decisions regarding segmenting, targeting, and positioning. This research aims to analyze (1) The application of segmentation, targeting, and positioning was used by tapai Gambut sellers to improve their business. (2) Marketing activities of tapai Gambut sellers as a subject matter of Marketing Basics on STP Marketing materials at SMKN 3 Banjarmasin. This research used qualitative approaches and descriptive research. The subjects of the study were tapai Gambut sellers in Pematang Panjang Village of Banjar Regency of South Kalimantan. The source of the data was primary data. The data was obtained by using observations, interviews and documentation. The obtained data was analyzed by using Milles and Huberman's models. Based on the results of research was obtained: (1) Tapai Gambut Entrepreneurs of Pematang Village has implemented STP marketing (segmenting, targeting and positioning) strategies that are able to increase sales profits of tapai products. (2) Marketing strategies on the economic activities of Tapai Gambut sellers in Pematang Village can be used as a source of additional teaching material in the school, especially in the subjects of The Basics of Education on Basic Competence 3.7 Describing the basics of marketing in SMKN 3 Banjarmasin class XKeywords: Segmentation, targeting, positioning, teaching material, marketing